T Cell Receptor and Cytokine Signaling Can Function at Different Stages to Establish and Maintain Transcriptional Memory and Enable T Helper Cell Differentiation - Bevington, Sarah L.; Cauchy, Pierre; Withers, David R.; Lane, Peter J. L.; Cockerill, Peter N. (Frontiers in Immunology, 2017)
Experienced T cells exhibit immunological memory via a rapid recall response, responding to re-stimulation much faster than naïve T cells. The formation of immunological memory starts during an initial slow response, when naïve T cells become transformed to proliferating T blast cells, and inducible immune response genes are reprogrammed as active chromatin domains. We demonstrated that these active domains are supported by thousands of priming elements which cooperate with inducible transcriptional enhancers to enable efficient responses to stimuli. At the conclusion of this response, a small reservoir of these cells return to the quiescent state as long term memory T cells. We proposed that priming elements can be established in a hit-and run-process dependent on the inducible factor AP-1, but then maintained by the constitutive factors RUNX1 and ETS-1. This priming mechanism may also function to render genes receptive to additional differentiation-inducing factors such as GATA3 and TBX21 that are encountered under polarizing conditions. The proliferation of recently activated T cells, and the maintenance of immunological memory in quiescent memory T cells, are also dependent on various cytokine signaling pathways upstream of AP-1. We suggest that immunological memory is established by T cell receptor signaling, but maintained by cytokine signaling.